1978
DOI: 10.1029/jb083ib04p01829
|View full text |Cite
|
Sign up to set email alerts
|

The control of volcanic column heights by eruption energetics and dynamics

Abstract: The height reached by a volcanic eruption column, together with the atmospheric wind regime, controls the dispersal of tephra. Column height is itself a function of vent radius, gas exit velocity, gas content of eruption products, and efficiency of conversion of thermal energy contained in juvenile material to potential and kinetic energy during the entrainment of atmospheric air. Different heights will be attained for the same total energy release depending on the style of the eruption: a discrete explosion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(212 citation statements)
references
References 28 publications
10
189
0
Order By: Relevance
“…Theoretical studies (Morton et al, 1956) indicate that H T should increase with the fourth root of eruption rate, and empirical compilations (Settle, 1978;Sparks et al, 1997, Chapter 5;Wilson et al, 1978) roughly follow this relationship Figure 1 plots plume height H T or H U (km) versus average eruption rate for the eruptions in Table 1.…”
Section: Plume Height Versus Eruption Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies (Morton et al, 1956) indicate that H T should increase with the fourth root of eruption rate, and empirical compilations (Settle, 1978;Sparks et al, 1997, Chapter 5;Wilson et al, 1978) roughly follow this relationship Figure 1 plots plume height H T or H U (km) versus average eruption rate for the eruptions in Table 1.…”
Section: Plume Height Versus Eruption Ratementioning
confidence: 99%
“…The observations from which these numbers were extracted are detailed in an accompanying document (Mastin et al, in preparation). Some entries were also compiled by previous authors (Carey and Sigurdsson, 1989;Sparks et al, 1997, Table 5.1; Wilson et al, 1978). Our compilation includes only events of the past century or so, excludes one from previous tables (Bezymianny, 1956) that is now known not to have produced a Plinian column (Belousov et al, 2007), and added some (e.g.…”
Section: Observations and Uncertaintiesmentioning
confidence: 99%
“…All of the first-order models of buoyant volcanic plume dynamics [Wilson et al, 1978 and that no mass is lost as a result of sedimentation or rainout.…”
Section: The Modelmentioning
confidence: 99%
“…A major outcome of the early modeling work was the demonstration that the maximum height to which a plume will rise is determined almost completely by the mass eruption rate of magma from the vent [Settle, 1978;Wilson et al, 1978]; it is the single most important parameter controlling the dispersal of particles, aerosols and gases and is the most useful quantity to know in any investigation of a plume's eruptive history and likely future behavior. Conversely, knowledge of the height of an eruption plume provides important information on the magma eruption rate.…”
Section: Paper Number 1998jb900047mentioning
confidence: 99%
“…Progressively more detailed theoretical models of plume rise [Morton et al, 1956;Wilson, 1976;Wilson et al, 1978;Sparks, 1986;Wilson and Walker, 1987;Woods, 1988;Glaze et al, 1997] have shown that the development of eruption plumes is generally a complex process. Despite evidence that the ash and gas components of some plumes may separate, ultimately rising to different altitudes [Holasek et al, 1996b;Seftor et al, 1997], all of these models assume well-mixed plumes where the ash and gas rise confluently.…”
Section: Introductionmentioning
confidence: 99%